Large pondweed beds potametalia - Szirmai Orsolya; Vas Mihály; Tuba Zoltán; Körmöczi László (2019)
Potametalia association order consists of the broadleaved rooted pondweeds of still- and slowly floating water bodies with depth of several meters. Several species occurring in this order are purely aquatic plants while other species can be present in terrestrial forms (amphibian plants). Large pondweed beds (Potamion lucentis) are the pioneer communities in the eutrophization processes.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok; Biológiai tudományok